Application of the Levenshtein Distance Algorithm in Searching for Data Advocates in Bengkulu City - Iis Dahlia; Siswanto Siswanto; Aji Sudarsono (GATOTKACA Journal (Teknik Sipil, Informatika, Mesin dan Arsitektur), 2021)
In this study, the development of a system that is able to assist the community in searching for advocates / lawyers, especially in Bengkulu City is carried out. Where the community enters the case they are experiencing, then matches the case that has been handled by an advocate in Bengkulu City. This match process is through the Levenstein Ditance algorithm approach. The final match result will be given to the public who are looking for a lawyer in the form of a match percentage level of the case handled. The Advocate Data Search Application in Bengkulu City was created using the PHP programming language and MySQL database. In the application, the Levenstein Distance Algorithm has been applied to make it easier to find advocate data by looking at the highest percentage level. In the process of searching for advocate data, the public enters the keyword of the case that is being experienced, then the system will read the keyword by comparing the case data that has been handled by the advocate in the database, resulting in a percentage level for each record in the database. In the Advocate Data Search Application in Bengkulu City, there are 2 access rights, namely Administrator and Community, each of which has different features. Based on the results of the tests that have been carried out, the Advocate Data Search Application in Bengkulu City has been running properly and the application is able to display search results through the stages of the Levenstein Distance Algorithm.